Microbial Electrochemical Oxidation of Anaerobic Digestion Effluent From Treating HTC Process Water - Dai, Shixiang; Korth, Benjamin; Vogt, Carsten; Harnisch, Falk (Frontiers in Chemical Engineering, 2021)
Hydrothermal carbonization (HTC) is a promising technology for chemical and material synthesis. However, HTC produces not only valuable solid coal-like materials, but also yields process water (PW) with high chemical oxygen demand (COD) that requires extensive treatment. Anaerobic digestion (AD) has been used for initial treatment of HTC-PW, but the AD effluent is still high in COD and particles. Here, we show that microbial electrochemical technologies (MET) can be applied for COD removal from AD effluent of HTC-PW. Bioelectrochemical systems (BES) treating different shares of AD effluent from HTC-PW exhibited similar trends for current production. Thereby, maximum current densities of 0.24 mA cm-2 and COD removal of 65.4±4.4% were reached (n=3). Microbial community analysis showed that the genus Geobacter dominated anode biofilm and liquid phase of all reactors indicating its central role for COD oxidation and current generation.